2016
DOI: 10.17221/3/2016-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary magnesium, calcium, phosphorus, and limestone grain size on productive performance and eggshell quality of hens

Abstract: ABSTRACT:Two experiments conducted on laying hens, aged 50 and 52 weeks, were carried out to evaluate the effect of dietary Mg and its relationship to the Ca : NPP (non-phytate phosphorus) ratio using a various grain-size of limestone. The Ca : NPP ratio in each experiment was 12.8 and 18, respectively. Two Mg levels were evalued in the first (1.56 and 4.0 g/kg) and the second experiment (1.52 and 4.0 g/kg). A fine-grained limestone (< 0.5 mm; FL) or a coarse-grained limestone (0.8-2 mm; CL) was used in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…Under heat‐ stress exposure, when Vit B6 and Mg used separately as a single supplement, there was no significant increase in EW, however, using the combination of Vit B6 and Mg there was significant increase in EW. In a study by M. Skrivan et al ( 2016 ), they found that increasing the level of dietary Mg (1.52 to 4.0 g/kg diet) increased EW significantly which is not consistent with our results. The source (MgO) and the amount of Mg should be taken into account that may be the reason for this discrepancy.…”
Section: Resultscontrasting
confidence: 99%
“…Under heat‐ stress exposure, when Vit B6 and Mg used separately as a single supplement, there was no significant increase in EW, however, using the combination of Vit B6 and Mg there was significant increase in EW. In a study by M. Skrivan et al ( 2016 ), they found that increasing the level of dietary Mg (1.52 to 4.0 g/kg diet) increased EW significantly which is not consistent with our results. The source (MgO) and the amount of Mg should be taken into account that may be the reason for this discrepancy.…”
Section: Resultscontrasting
confidence: 99%
“…The individual weight of each egg component was used to calculate the proportion of shell, yolk, and albumen from the egg weight. A QCT shell thickness micrometer (TSS York) was used to determine the egg shell thickness using the method described by Skrivan et al (2016). Haugh unit score was evaluated with a QCH apparatus (TSS York).…”
Section: Doi: 1017221/22/2017-cjasmentioning
confidence: 99%
“…2016; Skřivan et al . 2016). These earlier studies demonstrate that grit plays a critical role in digestive function not only in mechanically processing food, but also in supplying necessary minerals and helping to clean the digestive tract (Gionfriddo & Best 1999; Wings 2007; Downs et al .…”
Section: Taxon Specimen No Referencesmentioning
confidence: 99%